Contribution of Green Marketing to Brand Loyalty - Kuek, Way Teng (2013)
Green marketing has been around for more than 3 decades. It has bloomed in the 1980s, fell in the 1990s and then resuscitated in the 2000s. Many organizations had since integrated green marketing into their businesses. Many researchers had been performed to relate green marketing with revenue. However, there are not many references on the contribution of green marketing’s dimensions such as green design, green logistic, green pricing, green targeting and green positioning to brand loyalty. This research aimed to explore the relationship between dimensions of green marketing with brand loyalty. Hypotheses and online questionnaires were form and constructed based on literature review. Online survey form were then developed and distributed through online media. The collected responses were then analyzed using SmartPLS to examine and validate the hypotheses constructed. The analysis showed that green marketing dimensions of green pricing, green targeting and green positioning had no significant relationship to brand loyalty. Green marketing dimensions of green design and green logistic showed significant relationship to brand loyalty with green logistic being the most significant. Consumers were also shown to be prone to repeat their purchases just based on the product design while product logistics ensured consumers to stay with the product for a longer period.